1996
DOI: 10.1111/j.1151-2916.1996.tb09054.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Low‐Temperature Sintering of Reactive Mn‐Zn Ferrite Powder

Abstract: Highly sinterable Mn‐Zn ferrite powder consisting of sub‐micrometer‐size particles with structural distortion has been prepared by grinding a coprecipitated powder with a media agitation mill. Dense pure Mn‐Zn ferrites (>98% of theoretical) with an average grain size of 1.9 μm can be fabricated by heating at 900°C in a stream of N2. They show high permeability of 820 at 10 kHz through 1 MHz and an electric resistivity of 50 Ω cm at 1 kHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, CoZnFe 2 O 4 is not completely inverse, and the degree of inversion depends on the heat treatment. The spinel ferrite Mg Fe 2-x Cr x O 4 was also studied by Mossbauer spectroscopy over a wide range of temperatures [4]. The spinel ferrites Zn x Ni 5/3-x Fe 1 Sb 1/3 O 4 were also studied [5] by Mossbauer spectroscopy over a wide range of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…However, CoZnFe 2 O 4 is not completely inverse, and the degree of inversion depends on the heat treatment. The spinel ferrite Mg Fe 2-x Cr x O 4 was also studied by Mossbauer spectroscopy over a wide range of temperatures [4]. The spinel ferrites Zn x Ni 5/3-x Fe 1 Sb 1/3 O 4 were also studied [5] by Mossbauer spectroscopy over a wide range of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that electromagnetic properties of the multilayer chip ferrite components [9,18,[20][21][22] are influenced by the internal stresses and the diffusion of Ag buried in ferrite [23][24][25][26][27][28][29][30]. As the magnetostriction of MgCuZn ferrites is lower than that of NiCuZn ferrites, it was expected that the multilayer chip inductor using MgCuZn ferrite [31] would show higher magnetic properties than that using NiCuZn ferrite.…”
Section: Introductionmentioning
confidence: 99%